PALM OIL INDUSTRY WASTE WATER TREATMENT WITH COAGULATION METHOD, FENTON AND ADSORPTION - Jauhari, Taufiq; Trisnaliani, Lety; Purnamasari, Indah (KINETIKA, 2013)
Crude palm oil waste water is waste water that resulted from the palm oil industry. If crude palm oil waste water is released to environment, so it can decrease enviromentset quality  because it contains pollutant organic compound. In this research waste water crude palm oil processed using alum as coagulant with dosage 5000 ppm. This step process was continued by using the concentration fenton Fe2SO47H2O 0.004 M and concentration H2O2 0.32 M. In the final process waste water was treated  by adsorpstion active carbon columb of 30 cm, 40 cm and 50 cm and flow rate 80 mL/minute, 110 mL/minute and 140 mL/minute. In flow rate of  80 mL/minute and height activated carbon columb 50 cm the BOD, COD and TSS reduction increased until 70.10 %, 59.37 % and 85.69 % respectively.